Retzius‐sparing versus standard robot‐assisted laparoscopic prostatectomy for the treatment of clinically localized prostate cancer. (6th May 2021) - Rosenberg, Joel E.; Jung, Jae Hung; Edgerton, Zach; Lee, Hunju; Lee, Solam; Bakker, Caitlin J.; Dahm, Philipp
Abstract : Objectives: To assess the effects of Retzius‐sparing (RS) robotic‐assisted laparoscopic prostatectomy (RALP) compared to standard RALP for the treatment of clinically localized prostate cancer. Methods: We performed a systematic search of multiple databases and the grey literature with no restrictions on the language of publication or publication status, up until June 2020. We included randomized controlled trials (RCTs) comparing RS‐RALP with standard RALP. We performed a meta‐analysis using a random‐effect model. The quality of evidence was assessed on an outcome basis according to the Grades of Recommendation, Assessment, Development and Evaluation (GRADE) approach. Results: Our search identified six records of five unique RCTs, of which two were published studies, one was in press, and two were abstract proceedings. There were 571 randomized participants, of whom 502 completed the trials. The mean age of participants was 64.6 years and the mean prostate‐specific antigen level was 6.9 ng/mL. Approximately 54.2% of participants had cT1c disease, 38.6% had cT2a‐b disease, and 7.1% had cT2c disease. RS‐RALP probably improves continence within 1 week after catheter removal (risk ratio [RR] 1.74, 95% confidence interval [CI] 1.41–2.14; I 2 = 0%; studies = 4; participants = 410; moderate‐certainty evidence). Assuming 335 per 1000 men undergoing standard RALP are continent at this time point, this corresponds to 248 more men per 1000 (137 more to 382 more) reporting continence recovery. RS‐RALP may increase continence at 3 months after surgery compared to standard RALP (RR 1.33, 95% CI 1.06–1.68; I 2 = 86%; studies = 5; participants = 526; low‐certainty evidence). Assuming 750 per 1000 men undergoing standard RALP are continent at this time point, this corresponds to 224 more men per 1000 (41 more to 462 more) reporting continence recovery. We are very uncertain about the effects of RS‐RALP on serious adverse events compared to standard RALP (RR 1.40, 95% CI 0.47–4.17; studies = 2; participants = 230; very low‐certainty evidence). Conclusions: The findings of this review indicate that RS‐RALP may result in better continence outcomes than standard RALP up to 6 months after surgery. Continence outcomes at 12 months may be similar. The disadvantages of RS‐RALP may be higher positive surgical margin rates. We are very uncertain about the effect on biochemical recurrence‐free survival and potency outcomes. Longer‐term oncological and functional outcomes are lacking, and no preplanned subgroup analyses could be performed to explore the observed heterogeneity. Surgeons should discuss these trade‐offs and the limitations of the evidence with their patients when considering this approach.